2017
DOI: 10.15173/ijsap.v1i1.3119
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Students as Partners in Higher Education

Abstract: “Students as Partners” (SaP) in higher education re-envisions students and staff as active collaborators in teaching and learning. Understanding what research on partnership communicates across the literature is timely and relevant as more staff and students come to embrace SaP. Through a systematic literature review of empirical research, we explored the question: How are SaP practices in higher education presented in the academic literature? Trends across results provide insights into four themes: the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
376
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 399 publications
(394 citation statements)
references
References 6 publications
13
376
0
5
Order By: Relevance
“…While there are many examples and significant discussion in the research literature of partnership and co-creation projects involving small numbers of students, there are relatively few examples in the international literature of whole-class co-creation in learning and teaching within higher education (Bryson et al 2015;Mercer-Mapstone et al 2017). This lack of attention to pedagogically embedded forms of co-creation between a teacher and a whole class of students is a distinct weakness in the current literature, which this paper aims to highlight.…”
Section: Whole-class Approaches To Co-creation In Learning and Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are many examples and significant discussion in the research literature of partnership and co-creation projects involving small numbers of students, there are relatively few examples in the international literature of whole-class co-creation in learning and teaching within higher education (Bryson et al 2015;Mercer-Mapstone et al 2017). This lack of attention to pedagogically embedded forms of co-creation between a teacher and a whole class of students is a distinct weakness in the current literature, which this paper aims to highlight.…”
Section: Whole-class Approaches To Co-creation In Learning and Teachingmentioning
confidence: 99%
“…In higher education, there has been rising interest in research and practice about 'students as partners' and co-created learning and teaching (Cook-Sather et al 2014;Dunne 2016;Mercer-Mapstone et al 2017). Although relatively widespread, this work has taken place predominantly in the USA, Canada, UK, Australia, and Scandinavia, and Dunne (2016) highlights that people are using many terms to describe this work.…”
Section: Introduction To Co-creating Learning and Teachingmentioning
confidence: 99%
“…Indeed, Mercer-Mapstone et al (2017) found that most SaP work reported in their literature review took this form. Bourdieu's (1988Bourdieu's ( , 2003 theorising on power in societal structures, including universities, illuminated the role of habitus, or our unconsciously formed habits, dispositions, and preferences that are both influenced by our position in society, while also influencing our preferences and choices in our daily lives.…”
Section: Fostering Inclusive Partnershipsmentioning
confidence: 99%
“…Without expert contribution, OER repositories risk relying on lower quality materials from volunteers who may have time but not expertise. Furthermore, equal contribution of students and educators is paramount to the success of BStudents as Partners^educational projects, where the importance of reciprocity and inclusivity between students and educators has been identified across literature (Mercer-Mapstone et al 2017). ORPs should be designed to boost contribution rates and usage rates of both students and educators for healthy adoption.…”
Section: Current Usage and Upload Ratesmentioning
confidence: 99%